Branding as Communication: Understanding Students in Continuing to Open and Distance University - Sri Sedyaningsih; Imam Nuraryo; Gunawan Wiradharma; Melisa Arisanty (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2023)
Although branding is now widespread among Indonesian universities, the application of branding principles in the higher education sector is comparatively recent and may be controversial for internal audiences who question its suitability and efficiency. Universities need to communicate these characteristics effectively and consistently to all of the relevant stakeholders. This study explains the influence or impact of brand awareness and brand association on the interest in continuing their studies of high school students from three areas in Indonesia, especially Universitas Terbuka (UT). This survey used 812 respondents in random clusters from three senior high school regions from three regions of Indonesia, namely Bandung representing the western area, Makassar (middle area), and Jayapura (east area). The quantitative research approach was taken as the method of this research, through pilot testing, validity, and reliability testing with the hypothesis that there is a positive relationship between brand awareness, brand association, and interest in continuing open and distance learning studies in Indonesia. The results showed that the respondents' responses indicated that the brand awareness at Universitas Terbuka as a whole is quite good, especially for brand unaware and top of mind. Both simultaneously and partially, brand awareness and brand association significantly affect interest in continuing studies at Universitas Terbuka.